2019
DOI: 10.1007/s12571-019-00969-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavioural impact of an integrated home garden intervention: evidence from Bangladesh

Abstract: Integrated home garden interventions combine training in gardening practices with education about nutrition knowledge. Such interventions have been shown to improve nutrition behaviour in low income countries. However, to date rigorous evidence is lacking for their long-term impact. We test the impact of an integrated home garden intervention on vegetable production and consumption three years after the intervention ended. We analyse three rounds of survey data for 224 control and 395 intervention households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 34 publications
3
50
1
Order By: Relevance
“…Integrating agriculture and nutrition by addressing food security while emphasizing the importance of diverse, nutrient-dense foods for infant growth and development has potential benefits. Interventions combining homestead food production and behavior change strategies for complementary feeding practices reported positive results on vegetable production as well as children's nutritional status ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating agriculture and nutrition by addressing food security while emphasizing the importance of diverse, nutrient-dense foods for infant growth and development has potential benefits. Interventions combining homestead food production and behavior change strategies for complementary feeding practices reported positive results on vegetable production as well as children's nutritional status ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In some countries, the home garden development program to grow vegetables shows good sustainability and effectiveness in increasing vegetable intake. 73,74 This program has the potential to reduce the percentage of obesity. 75 The success of the program is supported by the integration of the yard development program and regular nutrition education, accompanied by the problem-solving assistance in dealing with technical obstacles in planting.…”
Section: Discussionmentioning
confidence: 99%
“…Low availability may explain why the Bhutan study found a positive association between home gardens and children's vegetable consumption. Other studies also demonstrated that home garden interventions can increase household vegetable production and consumption in the South Asian context ( Baliki et al, 2019 ; Bird et al, 2019 ; Osei et al, 2016 ; Schreinemachers et al, 2016 ).…”
Section: Introductionmentioning
confidence: 93%